2001
DOI: 10.1002/jid.726
|View full text |Cite
|
Sign up to set email alerts
|

Are user charges efficiency‐ and equity‐enhancing? A critical review of economic literature with particular reference to experience from developing countries

Abstract: User charges have come to play a significant role in the financing and delivery of publicly provided health services in many developing countries. As a response to health care financing crises, user charges are often promoted as a way of rationalizing the use of care, raising revenue, and improving the coverage and quality of services. The primary purpose of this paper is to provide a critical review of the main arguments for the efficiency- and equity-enhancing potential of user charges. The extent and scope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 67 publications
(131 reference statements)
2
36
0
Order By: Relevance
“…Our experience reflects other studies which show that even when well implemented, exemption systems based on individual or household targeting, in contexts where a large proportion of the population is too poor to pay, do not include all those in need of financial assistance to access care. 35,36 Fifth, MSF experience has shown that in contexts with widespread poverty, alternatives to cost recovery systems that incur even a modest fee from service users (e.g. a low flat fee, free drugs but continued payment of other treatment costs, and targeted household or individual exemptions) continue to act as a financial barrier to healthcare access for some, especially the poorest and most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience reflects other studies which show that even when well implemented, exemption systems based on individual or household targeting, in contexts where a large proportion of the population is too poor to pay, do not include all those in need of financial assistance to access care. 35,36 Fifth, MSF experience has shown that in contexts with widespread poverty, alternatives to cost recovery systems that incur even a modest fee from service users (e.g. a low flat fee, free drugs but continued payment of other treatment costs, and targeted household or individual exemptions) continue to act as a financial barrier to healthcare access for some, especially the poorest and most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, beyond a certain threshold, households are understandably unable to cope with the continuing financial burden of treatment. Although a social waiver system was in place to identify and exempt individuals who were unable to pay, the experience with waiver systems in settings where the median income is well under absolute poverty is that they are insensitive in detecting 'ability to pay' and thus repeatedly fail (Sepehri and Chernomas, 2001). The fact that five patients in our study diluted ART doses in order reduce the monthly cost of medication by half suggests that the waiver system failed to provide sufficient support to those unable to pay and could not be calibrated to adjust for fine changes in the ability to pay.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of patient co-payments on access to care, utilisation of services and health outcomes, and the implications for public policy of patient co-payments, have been the focus of much attention in the international health policy literature over many years (Scitovsky and Sneider, 1972;Rice and Morrison, 1994;Sepehri and Chernomas, 2001). The issue is of particular salience in New Zealand, where primary health care traditionally has been only partially subsidised by government, resulting in individual New Zealanders cofunding their access to primary health care through significant out-of-pocket payments, with the level of co-payments traditionally set by general practitioners (GPs), in an unregulated market setting.…”
Section: Introductionmentioning
confidence: 99%